Valorization of phosphogypsum as a thermal energy storage material for low temperature applications. (15th March 2022) - Anagnostopoulos, Argyrios; Navarro, M.; Ahmad, A.; Ding, Yulong; Gaidajis, G.
Abstract: Phoshpogypsum (PG) is an industrial byproduct of the fertilizer industry typically disposed in the sea, dams or dykes, which presents a significant environmental hazard due to elevated content in radioactive heavy metals. Only 15% of it is recycled, and to this end, a novel circular economy case is proposed. The PG is combined with a commercial-grade paraffin to fabricate composite phase change materials (CPCMs). No variation in latent heat and melting point are observed after 96 cycles (25 to 100 °C) denoting good thermal stability. Maximum latent heat is 75 J/g (60% paraffin content), while the optimal average specific heat capacity is 1.54 J/gK for the same paraffin content. The thermal conductivity is found to be up to 0.46 W/mK; 75% higher than pure paraffin. The maximum energy storage density is 237 MJ/m 3; only 14% lower than the pure paraffin. A lab scale TES layout of the PG based CPCMs is also investigated in ANSYS. The effect of the flow rate of the heat transfer fluid, in this case air, is evaluated. A maximum charge and discharge efficiency of 88.1% and 66.2% respectively, is achieved for flow rates of 5.5 and 22 L/min correspondingly. Graphical abstract: Image 1 Highlights: A novel phase change material consisting of PG and paraffin is presented. Good chemical compatibility and thermal stability are observed after 96 cycles. Optimal average thermal conductivity of 0.46 W/mK; 74.93% higher than pure paraffin. Energy storage density is 237 MJ/m 3 (25–100 °C); only 14.04% lower than the pure paraffin. Simulated maximum lab scale discharge efficiency is found to be 88.11%.